Relationships among corporate website quality, user satisfaction and behavioural loyalty / Sandra Rangai Balang - Rangai Balang, Sandra (2013)
This study aimed to examine how corporate website quality would affect the users’ satisfaction and behavioral loyalty. Besides that, the role of frequency of website visit was also investigated to understand its influences on the relationships of corporate website quality, users’ satisfaction and their behavioral loyalty. The research was based on survey data. The instrument adapted the website quality dimensions as proposed by Aladwani and Palvia (2002) and 7-point Likert scale was used. The duly designed questionnaire was validated by experts and pre-tested. The survey yielded 1200 usable questionnaires from various places in Malaysia using quota sampling. The corporate websites evaluated were selected randomly from the public-listed companies in Malaysia. Exploratory factor analysis was used to assess the measures and results indicated that the measurement was reliable and valid. Further statistical analyses included relevant descriptive analyses, independent sample T-test, ANOVA, and multiple regression analyses. The results indicated that there were positive relationships among corporate website quality, user satisfaction and behavioral loyalty. It was found that the relationships between corporate website quality, user satisfaction and behavioral loyalty were weaker with the existence of frequency of website visit as a moderator.